Hegel’s Concept of Right - Horn, Christoph (ETHICS IN PROGRESS, 2022)
This article examines the foundations for the legitimacy of law from the perspective of Hegel’s philosophy. In a first step, Kant’s justification of law is discussed, as Hegel takes the Kantian model as a central point of (critical) reference. Then, in the Section 2, I discuss Hegel’s reasons for rejecting the main strategies of justification of the legal order: natural law, contractarianism and legal positivism. This is further followed by a discussion of the meaning and scope of Hegel’s contextualism, according to which there can be no practical normativity without a certain historical embedding. Finally, I describe a more traditional met-aphysical reading (supported among others by Kevin Thompson) that I consider to be the correct solution, contrasting it with Honneth’s theory of recognition and Bran-dom’s pragmatism.